STUDI KOMPARASI LAMA PERAWATAN PASIEN DENGAN DEMAM TIFOID YANG DISEBABKAN OLEH STRAIN SALMONELLA TYPHI NON-MDR DAN MDR TERHADAP ANTIBITIK DI RSUD dr. SOETOMO SURABAYA - Erika Martining Wardani; Handayani . (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
This analytic observational study aim was to find correlation between length of treatment oftyphoid fever patients and type of Salmonella typhi strain that are Non MDR and MDR in the period of2012–2015 at dr. Soetomo Hospital. This research using cohort retrospective design using secondarydata from medical record. The sample were 30 case non-MDR Salmonella typhi and 30 case MDRSalmonella typhi. Laboratory result were compiled from Clinical Microbiology Installation whilelength of treatment data were compiled from Medical Record Unit at dr. Soetomo Hospital. Mosttyphoid patient in dr. Sutomo hospital were under 12 years old (53,3%) and male sex (55%). Thepatients with MDR typhoid fever have hospitalized duration longer than non MDR typhoid. 83.3% ofMDR typhoid patients hospitalized duration were 7–14 days, 10% < 7 days, and 6.7% >14 days.63.3% non-MDR typhoid patients hospitalized duration were < 7 days, and 36.7% in 7–14 days. Crosstabulation analysis showed significant different in patient age (p value = 0,008), hospitalized duration (p value = 0,000) between the two groups. It could be concluded that hospitalized duration oftyphoid fever patients have correlations with the type of Salmonella typhi strain non-MDR or MDR